The design of the roof crowns for old mosques in Malacca / Iman Syaidatul Izzati Abd Rahman ... [et al.] - Abd Rahman, Iman Syaidatul Izzati; Zainal, Murni; Ismail, Iznny; Ahmad Fuad, Farah Hanna (2023)
The mosque is an important institution for the spiritual, social, culture and economic development of the Muslim community. Discovered thirty-eight (38) number of mosques with unique roof crown or “Mahkota Atap Masjid” in Malacca due to decorative elements on its roof that depict the richness of the culture, history, identity, and hallmark of Islam in Malacca. However, the uses of ornament roof crown that can be seen at some of mosques in Malacca have been decreased, and now replaced with the dome. The objectives of this research are, i) to analyze the significance of the ornament roof crowns by knowing the history and background behind prominent old mosques in Malacca that influence their roof crown design and ii) to find the differences and similarities of the prominent old mosque’s roof crown design to the typologies classification (layered), form of structure, color, and motifs. Qualitative methodology was applied using three (3) case studies in Malacca; i) Kampung Hulu Mosque (built in1892), ii) Terengkera Mosque (built in 1511) and iii) Kampung Keling Mosque (built in 1748). Observation studies are focus on the design and characteristics of the ornament roof crowns. Results, show obvious similarities on the balance and uniformity to the various cultures and all these are unified by one (1) believed in tawhid, although these three (3) mosques have been built in different eras. The differences can be seen through the complexity of motif’s carving, which the earliest crown of Tengkera Mosque that built in year 1511, had the finest motifs that depicted the richness of culture from various foreign cultures are finely carved at place of Muslim worship in Malacca.